Evaluation of miR-15a, miR-16-1, ZAP-70, Ang-2, and Bcl-2 as potential prognostic biomarkers in chronic lymphocytic leukemia - Tatiane Vieira Braga; Fernanda Cristina Gontijo Evangelista; Marie Gabriele Santiago; Aline Lúcia Menezes Ferrão; Tamara Dauare de Almeida; Bárbara Lima da Fonseca Barbosa; Sergio Schusterschitz da Silva Araujo; Glaciano Nogueira Ribeiro; Maria das Graças Carvalho; Adriano de Paula Sabino (Universidade de São Paulo, 2022)
Abstract Chronic lymphocytic leukemia (CLL) is a blood cancer characterized by the accumulation of clonal B-lymphocytes. This study evaluated the mRNA gene expression of miR-15a, miR-16- 1, ZAP-70, and Ang-2 by qPCR, as well as the plasma levels of Bcl-2 by Elisa immunoassay, in CLL patients and healthy controls. Significant differences were observed when comparing patients and controls regarding miR-15a (p < 0.001), miR-16-1 (p < 0.001) mRNA, Ang-2 gene expression, and Bcl-2 plasma levels (p < 0.001). When stratified by risk, differences were maintained with a significantly reduced expression in high-risk patients. A positive correlation was observed between miR-15a and platelets (R2 = 0.340; p = 0.009) as well as between Bcl-2 and leukocytes (R2 = 0.310; p = 0.019). Conversely, negative correlations were observed between ZAP-70 and platelets (R2 = - 0.334; p = 0.011), between miR-15a and lymphocytes (R2 = - 0.376; p = 0.004), as well as between miR-16-and lymphocytes (R2 = - 0.515; p = 0.00004). The data suggest that a reduction in miR-15a and miR-16-1 expressions, in addition to an overexpression of Bcl-2, are associated with the reduction in apoptosis and, consequently, to a longer survival of lymphocytes, thus contributing to lymphocyte accumulation and aggravation of the disease. By contrast, Ang-2 expression was significantly higher in A than in B + C Binet groups. This context leads to the speculation that this biomarker should be investigated in more robust studies within populations with a still relevantly indolent form of the disease in an attempt to identify those patients with a greater potential for an aggravation of the disease.